2001
DOI: 10.1126/science.291.5501.106
|View full text |Cite
|
Sign up to set email alerts
|

Toward Separation and Purification of Olefins Using Dithiolene Complexes: An Electrochemical Approach

Abstract: The complex Ni[S2C2(CF3)2]2 reacts with light olefins, including ethylene and propylene, selectively and reversibly. The reaction is not poisoned by hydrogen gas, carbon monoxide, acetylene, or hydrogen sulfide, which are commonly present in olefin streams, presumably because olefin binding occurs through the sulfur ligand rather than the metal center. The reversible reaction of olefins with Ni[S2C2(CN)2]2n (n = 0, -1, -2) can be controlled electrochemically, where the oxidation state-dependent binding and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
228
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(248 citation statements)
references
References 23 publications
19
228
1
Order By: Relevance
“…Apparently, there is a significant need to develop novel alternative C 2 H 2 /C 2 H 4 separation approaches. Some recent attempts, hydrogenation by non-precious metal alloy catalysts 44 , ionic liquid extraction 45 , and π-complexation 46 , have been made to reduce the cost or to enhance the selectivities. The realization of our first example of microporous MOF materials for such challenging separation highlights the very promise of the emerging microporous MOFs to resolve this very important industrial separation task in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, there is a significant need to develop novel alternative C 2 H 2 /C 2 H 4 separation approaches. Some recent attempts, hydrogenation by non-precious metal alloy catalysts 44 , ionic liquid extraction 45 , and π-complexation 46 , have been made to reduce the cost or to enhance the selectivities. The realization of our first example of microporous MOF materials for such challenging separation highlights the very promise of the emerging microporous MOFs to resolve this very important industrial separation task in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ground-state formulation has a bearing on the reactivity of such complexes, since Stiefel and coworkers have found that similar compounds can selectively and reversibly bind olefins [16] with potentially large impact on industrial olefin separation processes. Clearly, the question whether ligand radicals persist in such complexes or not is at the heart of the formulation of a correct reaction mechanism.…”
Section: Ma C H T U N G T R E N N U N G (L Bumentioning
confidence: 99%
“…They have attracted the interest of scientists due to their special structural features and physical properties, which include novel catalytic, non-linear optical, conductive, fluorescent and magnetic properties [1][2][3][4][5][6][7]. Among these compounds, the transition metal complexes anion (based on the thiocyanate or isothiocyanate ligand) attracts much interest as these ions may coordinate either through the N or S atom as a monodentate ligand, or though N and S atoms as a bridging ligand, forming some complexes with one-, two-or three-dimensional networks [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%